Social And Private Partnership Through Contractual Arrangement; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Berkalov S. V. Sergey Vitalievich (2018, 2018)
Title screen